DOI: 10.12681/eadd/22308
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of early childhood education quality in Kenya

Abstract: Accomplishing a study of this nature is a momentous task that was made possible by the dedicated support of my supervisory committee. My heartfelt gratitude goes to my supervisor in-charge Professor Eugenia Koutsouvanou upon whose fruitful directions I relied extensively. The patience and dedication she demonstrated was inspirational.My gratitude goes to Professor Anna Frangoudaki and Professor Dimitra Makrinioti, members of my supervisory committee, for patiently guiding me throughout the construction of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…The findings indicated that participative leadership positively and significantly influenced the job satisfaction of academic staff. This finding is consistent with previous scholars (Usman et al, 2021;Merks, 2020;Dokony et al, 2020;Shegaw, 2020;Muganda & Muganda, 2020;Chan, 2019;Mwaisaka et al, 2019b;Hayat Bhatti et al, 2019;Dyczkowska & Dyczkowski, 2018) who indicated existence of a positive association between participative and job satisfaction. Therefore, this means that participative leadership behaviours at Kyambogo University enhance the job satisfaction of academic staff.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The findings indicated that participative leadership positively and significantly influenced the job satisfaction of academic staff. This finding is consistent with previous scholars (Usman et al, 2021;Merks, 2020;Dokony et al, 2020;Shegaw, 2020;Muganda & Muganda, 2020;Chan, 2019;Mwaisaka et al, 2019b;Hayat Bhatti et al, 2019;Dyczkowska & Dyczkowski, 2018) who indicated existence of a positive association between participative and job satisfaction. Therefore, this means that participative leadership behaviours at Kyambogo University enhance the job satisfaction of academic staff.…”
Section: Discussionsupporting
confidence: 93%
“…Studies (Usman et al, 2021;Merks, 2020;Dokony et al, 2020;Shegaw, 2020;Muganda & Muganda, 2020;Chan, 2019;Mwaisaka et al, 2019b;Hayat Bhatti et al, 2019;Dyczkowska & Dyczkowski, 2018) related participative leadership and job satisfaction of academic staff. From the above studies, a contextual gap emerged as all the studies were carried outside the University context in organisations such as the healthcare sector (Usman et al, 2021), telecommunication sectors (Dokony et al, 2020), tax revenue (Shegaw, 2020), secondary schools (Muganda & Muganda, 2020), retailing store (Chan, 2019) yet the employment dynamics of such organisations are far distinct from those in universities. This contextual gap thus called for this study that examined the association between the two variables in the context of Kyambogo University in Uganda.…”
Section: Leadership Behaviours and Job Satisfaction Of Academic Staffmentioning
confidence: 99%
“…The study adopted the following dimensions of dynamic capabilities: human resource, physical infrastructure and the distribution network, strong brand, technology, market research, innovation and manpower development and talent nurturing. Dynamic capabilities had a partial mediating effect on the relationship between quality management practices and performance while Muganda and Fadhili, (2018) revealed there is need to build dynamic capabilities and a framework that recognizes the key drivers that underlie the development of off-shoring success in IT industry in Kenya.…”
Section: Introductionmentioning
confidence: 99%